Systematic and Contractual Protection of the Commercial Establishment in the Saudi Legal System - Deif, Aser Mohamed Abou (Journal of Ecohumanism, 2024)
Although the Saudi Commercial Court Law does not specifically regulate commercial assets, the Saudi legislator has addressed the protection of such assets through the Competition Protection Law issued by Royal Decree No. 75 of the year 1440 AH. This law aims to protect merchants from any unfair competition that may affect their capital, or in other words, their commercial assets. In commercial jurisprudence, these assets are referred to as the "commercial establishment" or "store," which comprises both tangible and intangible movable assets owned by the merchant as a single unit. Moreover, there exists an alternative method of protecting the commercial establishment beyond the statutory framework, namely, the protection provided through contractual agreements. Merchants may include clauses in their contracts that prohibit competition that harms them, commonly referred to as "prohibited competition." Thus, there are two types of protection for the commercial establishment: the first is protection from unfair competition, regulated by law, and the second is protection from prohibited competition, regulated by contractual clauses.